Високовольтна установка для синтезу нановуглецю з onion-like структурою з системою керування електричними характеристиками газового розряду - Богуславський, Л. З.; Вінниченко, Д. В.; Назарова, Н. С. (НТУ "ХПІ", 2015)
Проведено аналіз умов, необхідних для електророзрядного синтезу нановуглецю. Обґрунтовано використання оптимальної системи керування електричними характеристиками газового розряду. Розроблено генератор високовольтних імпульсів, який дозволяє отримувати необхідний широкий діапазон електричних характеристик розрядних імпульсів. Розроблено базове технологічне рішення для реалізації електророзрядного високочастотного способу синтезу аморфногоа нановуглецю з onion-like структурою і виготовлено експериментальну високовольтну установку.

The authors conducted the analysis of the conditions required for an electric discharge synthesisf nanocarbon. The usage of optimal control system of gas discharge electrical characteristics was proved. A system for controlling electrical characteristics of the gas discharge was designed. Control system was performed using modern digital technologies. It provides the implementation of complex multileveled tasks of the process’ control. A high-voltage pulse generator was designed. It allows obtaining required wide range of discharge pulses’ electrical characteristics. The basic technology solution for the implementation of an electric high-frequency synthesis method of amorphous nanocarbon with onion-like structure was developed. The high-voltage experimental appliance was produced. Developed appliance allows to improve performance of pure nanocarbon up to 20 grams per hour.
High voltage processing unit for the synthesis of onion-like structured nanocarbon with the control system of gas discharge electrical characteristics
Keywords: електророзрядний синтез; аморфний нановуглець; система оптимального керування; вуглецеві наноматеріали; високовольтна технологічна установка; electric-discharge synthesis; amorphous nanocarbon; optimal control system; electrical characteristics; high-voltage processing unit